Fast filling strategy of type III on-board hydrogen tank based on time-delayed method. (18th August 2021) - Wu, Xian; Liu, Jitian; Shao, Jianwang; Deng, Guoming
Abstract: In order to study the fast filling problem of the type III on-board hydrogen tank, a 3D computational fluid dynamics (CFD) simulation model is proposed. Several simulation calculations are completed to simulate the fast filling process under different initial conditions. In order to control the temperature rise during the fast filling process, the effects of different mass flow rates are studied. Based on the control of mass flow rate, various time-delayed filling strategies for different conditions are proposed to meet the requirement of shortening the filling time as much as possible without exceeding the maximum temperature limit. It is found that if the delay duration is determined, how the filling time is allocated has little effect on the final temperature rise. The proposed strategy can complete the filling within 155s in a general environment, which saves 62% of the time compared with the filling with constant mass flow rate. This research provides the theoretical basis and technical support for mass flow control strategies of fast filling in the hydrogen refueling stations and has guiding significance for the actual filling process of large-capacity hydrogen tanks. Highlights: Delaying during the filling process can effectively suppress the temperature rise inside the hydrogen tank. Delay durations have significant effect on the temperature rise inside the hydrogen tank. The time allocation scheme of two-stage time-delayed filling has little effect on the temperature rise inside the tank.